STUDENT-LECTURER READINESS FOR ONLINE TEACHING AND LEARNING AMID AND BEYOND COVID-19 IN RURAL SOUTH AFRICAN HIGHER EDUCATION INSTITUTIONS - NDIVHUWO DOCTOR SUNDANI; AMUKELANI COLLEN MANGAKA (Social Sciences and Education Research Review)
It is recorded that coronavirus disease (Covid-19) caused massive disruption and significant change in higher education institutions (HEIs), especially in rural-based institutions. The study aims to discuss student-lecturer readiness for online teaching and learning in rural South African HEls in the midst of Covid-19 and beyond. Critical theory was adopted to support discussions of the study. A systematic literature review (SLR) was conducted to achieve the study's intended goal and to test the research questions. Therefore, the researchers used the "Preferred Reporting Items for Systematic Review and Meta-analysis" (PRISMA) guidelines. Thus, Google Scholar, EBSCOhost, ResearchGate, ScienceDirect, Sabinet, ProQuest, Cambridge Core, and Scopus were used by the researchers to retrieve and analyse information from scholarly documents such as peer-reviewed journal articles and conference papers (n=12) published between 2002 and 2023. The major findings of the study are based on the literature gathered by the researchers. The study's evidence shows that the pandemic has given rise to learning losses and increases inequality. It was recommended in this study that the government should provide technologies to help students and lecturers adjust to a new mode of teaching and learning.